2020
DOI: 10.1002/ptr.6964
|View full text |Cite
|
Sign up to set email alerts
|

Ginger (Zingiber officinale Roscoe) as a nutraceutical: Focus on the metabolic, analgesic, and antiinflammatory effects

Abstract: Ginger (from the rizhome of Zingiber officinale Roscoe) has been widely used in ethnomedicine for the cure of several ailments. Main active ingredients include phenolic compounds named gingerols. In modern phytotherapy, ginger preparations are predominantly used to counteract nausea and vomiting in pregnant women. However, a number of other pharmacological actions of potential therapeutic interest, which might broaden the spectrum of its clinical use, have been reported. This focused review aims at giving a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 95 publications
0
39
0
Order By: Relevance
“…Among the biologically active compounds of terpenes, gingerols are the most abundant [ 13 ], with 6-gingerols containing a high amount [ 14 ]: analytical analyses determined that the amount of 6-gingerols was between 57.67 and 62.64 mg/g of rhizome-methanol extract [ 15 ]. Gingerols are thermally labile at high temperatures and easily subject to dehydration to form shogaol.…”
Section: Ginger: Chemical Structure Properties and Therapeutic Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the biologically active compounds of terpenes, gingerols are the most abundant [ 13 ], with 6-gingerols containing a high amount [ 14 ]: analytical analyses determined that the amount of 6-gingerols was between 57.67 and 62.64 mg/g of rhizome-methanol extract [ 15 ]. Gingerols are thermally labile at high temperatures and easily subject to dehydration to form shogaol.…”
Section: Ginger: Chemical Structure Properties and Therapeutic Potentialmentioning
confidence: 99%
“…It has been demonstrated that after steam extraction, ginger contains a small percentage of essential oil rich in sesquiterpene hydrocarbons such as zingiberene and also small amounts of monoterpenic hydrocarbons and oxygenated compounds. However, attention must be paid when selecting the drying method or the freshness of the ginger, because these can affect the chemical structure and so alter the efficacy of the resulting compound [ 13 ]. Indeed, the main sesquiterpene hydrocarbon compounds in ginger oil obtained from fresh rhizome were α-zingiberene (27–30%), α-curcumene (8–9%), β-sesquifellandrene (4.8%), and bisabolen (3.2%).…”
Section: Ginger: Chemical Structure Properties and Therapeutic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles have recognizable activities against various mycotoxigenic fungi such as Bipolaris sorokiniana, Magnaporthe grisea, Botrytis cinerea, Candida albicans, C. tropicalis, Aspergillus spp., Fusarium spp., P. expansum, and Al. alternata [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The main active ingredient in ginger is a phenolic compound called gingerol. The composition contained in ginger is mostly used to treat nausea and vomiting in pregnant women in modern phytotherapy (Pagano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%